International Procurement Centre. Case Study: SONY TV Industries (Malaysia) Sdn. Bhd. / Amiruddin Shaharin - Shaharin, Amiruddin (1999)
This graduation exercise has been written to provide a clear view and practical understanding on the current scenario on activities carried out under International Procurement Centre ( I P C ) status by SONY TV Industries ( M ) Sdn Bhd ( SBN). The activities involve are sourcing, purchasing , repackaging and transport. The problem faces by SBN in order to run the activities are production matter, supplier related problem, lead time and claims by customer. Due to this problem, SBN had to bear extra cost of operation . Personal interviews and observations has been made in order to gain more information. Resulting from that , certain procedures are recommended in order to improve the situation